Genetic Diversity of Bananas (Musa spp.) in Pesawaran District, Lampung Province Based on Sequence Related Amplified Polymorphism (SRAP) Marker - Leni Agustin; Eti Ernawati; Lulut Dwi Sulistyaningsih; Mahfut (Jurnal Biologi Tropis, 2023)
Banana (Musa spp.) is a leading commodity that makes a major contribution to national fruit production. One of the districts in Lampung Province which has a significant contribution to Indonesia's banana production is Pesawaran Regency. The molecular marker used in this study is Sequence-Related Amplified Polymorphism (SRAP). This study aims to determine the genetic diversity of bananas, determine the suitable combination of SRAP primers to determine the genetic diversity of bananas and determine the similarity relationship of bananas in the Pesawaran District. The total genomic DNA was extracted using DNeasy Plant Mini Kit (Geneaid) according to the protocol from the manufacturer followed by their amplification using SRAP primers. Similarity analysis was carried out based on similarity index values and dendrogram construction using the NTSYS 2.0 program. Research results show that a total of 204 loci (167 polymorphic loci and 37 monomorphic loci) were obtained from 9 selected primer combinations. The genetic diversity of 19 banana cultivars originating from Pesawaran Regency resulted in low genetic diversity values (0-0.27). Banana kinship based on Sequence Related Amplified Polymorphism (SRAP) markers divided 19 banana cultivar samples and 4 wild banana samples into 2 large clusters with similarity coefficient values between 0.70-0.97.